Penerimaan Khalayak mengenai Gaya Hidup Hedonisme yang ditampilkan dalam Video Blog NRab Family - Brigitta Revia (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2019)
Hedonists is a behavior that is seen as a truth if the culprit feels a pleasure or pleasure. But, the hedonists have changed the concept of pleasure into happiness. One of the prominent characteristics possessed by the hedonists is to obtain happiness from mere pleasure and as far as possible away from unpleasant emotions. This hedonic lifestyle is being displayed in the mass media, one of which is youtube which is now a new media. This research then focuses on how good acceptance of the Hedonism Lifestyle is displayed on Youtube Channel NRab Family. By using the reception analysis method this research produces the position of the audience in interpreting the Hedonic message displayed by Youtube Channel NRab Family. The selected informant must know the artist Nia Ramadhani, once watched the NRab Family Vlog, and knows that Nia Ramadhani is married to Ardhi Bakri, an Indonesian conglomerate. Based on the results of data analysis and discussion it was found that the Hedonism Lifestyle displayed on the NRab Family Youtube Channel produced a result. On signs related to luxury lifestyles, the informant's acceptance is in a dominant position that they agree that the Youtube Channel NRab Family displays a luxurious lifestyle.